Influence of "Thireomagnile" and "Thyrioton" preparations on the antioxidant status of pregnant cows with symptoms of endotoxicosis - Grymak, Y.; Skoromna, O.; Stadnytska, O.; Sobolev, O.; Gutyj, B.; Shalovylo, S.; Hachak, Y.; Grabovska, O.; Bushueva, I.; Denys, G.; Hudyma, V.; Pakholkiv, N.; et al. (My University, 2020)
The purpose of this search was to investigate the influence of “Thireomagnile” and “Thyrioton” on the antioxidant status of cows in the development of endotoxicosis. The experimental part of the work was performed at the Department of Pharmacology and Toxicology of Stepan Gzhytskyj Lviv National University of Veterinary Medicine and Biotechnologies, in the laboratory of Pharmacology and Toxicology of the State Scientific Research Institute of Veterinary Preparation and Feed Additives (Lviv) and in the Ltd. “Barkom”, village Yampil of Pustomyty district, Lviv region. To solve the tasks of the research, three experimental groups of 10 pregnant cows of the Ukrainian Black-Spotted Dairy breed were formed in each: control and two experimental. Cows of the control group (K) had characteristic clinical signs of endotoxicosis. Animals of the first experimental group (E1) were given 10 mL per animal of “Thyroid magnet” at the eighth and ninth months of gestation. The animals of the second experimental group (E2) were given Thyrioton at a dose of 10 mL per animal in the eighth and ninth months of gestation. As a result of the conducted researches it is found out that in pregnant cows with clinical manifestation of endotoxicosis the inhibition of the activity of the antioxidant protection system and intensification of processes of lipid peroxidation occurs. The use of “Thireomagnile” and “Thyrioton” in cows by the development of endotoxicosis contributed to the increased activity of the antioxidant system, which is indicated by an increase in the activity of glutathione peroxidase, glutathione reductase and glucose-6-phosphate dehydrogenase. The use of of “Thireomagnile” and “Thyrioton” to cows in the development of endotoxicosis contributed to the suppression of lipid peroxidation processes, which is indicated by the low level of primary and final products of lipid peroxidation, namely: lipid hydroperoxides and TBA-active products. Better normalizing action on the equilibrium on the activity of the antioxidant system and the intensity of lipid peroxidation was shown by the introduction of “Thyroid magnet” at a dose of 10 cm3 per animal.
Keywords: Antioxidant protection system; Pregnant cows; Endotoxicosis; Preparation